Global health education at the U.K. medical schools and its implications to China - HOU Jianlin, KE Yang (Jichu yixue yu linchuang)
Medical schools in the United Kingdom are fully aware of the importance of global health education in cultivating future medical talents. Global health education has been integrated into medical education and with novo curriculum and implementation of smart teaching technology. The medical schools constantly update and improve learning outcomes of global health curriculum and achieved the goal of education reformation. Drawing on the relevant experience from the U.K., China should steadily develop global health education for medical students, strengthen the construction of global health courses and degree programs, enhance medical students' global health competence, and attach importance to the cultivation of high-level global health professionals.